2018
DOI: 10.15171/jrip.2019.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic resistance pattern of extended spectrum beta lactamase producing Escherichia coli isolated from urinary tract infection

Abstract: Introduction: Urinary tract infection (UTI) due to extended spectrum beta-lactamase (ESBL)-producing bacteria including Escherichia coli has become widespread. Studies have shown a trend toward higher mortality, longer hospitalization, greater hospital expenses and reduced rates of clinical and microbiologic response in ESBL UTI. Objectives: The aim of this study is to determinate the prevalence and antibiotic resistance pattern of ESBL producing E. coli isolated from UTI. Patients and Methods: This cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 9 publications
(9 reference statements)
6
13
0
Order By: Relevance
“…Due to the weakened immune system of burn patients, broad-spectrum antibiotics are used to treat bacterial infections in this group, which may increase the prevalence of antibiotic resistance (20). With the exception of carbapenems, the above results are consistent with other Iranian studies conducted in 2019 (21,22). The antibiotic resistance rate of E. coli strains in Turkey was also much lower than in the present study (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Due to the weakened immune system of burn patients, broad-spectrum antibiotics are used to treat bacterial infections in this group, which may increase the prevalence of antibiotic resistance (20). With the exception of carbapenems, the above results are consistent with other Iranian studies conducted in 2019 (21,22). The antibiotic resistance rate of E. coli strains in Turkey was also much lower than in the present study (20).…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that unlike amikacin, ampicillin is not suitable for the treatment of E. coli infections in Iran. Moreover, resistance to carbapenems among isolates collected from Bu-Ali Sina hospital in this study was similar to other studies in Iran and neighboring countries (13,19,21,22,25), while the reported carbapenem resistance rates in non-neighboring countries such as Malaysia and Nigeria were 29.2% and 19.7%, respectively (26,27). This discrepancies may be due to the differences in the type of sample, as Bu-Ali Sina hospital is a specialized pediatric hospital.…”
Section: Discussionsupporting
confidence: 90%
“…The first bacteria expressing acquired ESBL were identified in 1983 in Germany, and since 2000, ESBL-producing Escherichia coli (ESBL-EC) have spread throughout the world in both community and hospital settings (Kruglova & Stasheva, 2010;Rossignol et al, 2017;Rajabnia et al, 2019). Worryingly, the incidence of ESBL-EC continues to increase worldwide (Khanfar et al, 2009;Shakya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…β-Lactam antibiotics are the safest and most frequently prescribed antimicrobial agents for urinary tract infection (UTI) ( Magale et al., 2016 ). They are a class of broad-spectrum antibiotics that contain a beta-lactam ring in their molecular structure ( Ahmed et al., 2015 ; Rajabnia et al., 2019 ). Several studies prove the increased resistance of E. coli in UTI to beta-lactam antibiotics ( Glasner et al., 2013 ; Tacconelli et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation